2019
DOI: 10.4103/jfmpc.jfmpc_371_19
|View full text |Cite
|
Sign up to set email alerts
|

A survey on orthodontic services provided by general dental practitioners

Abstract: The aim of this survey-based study was to recognize professional determinants that account for variations in the level of orthodontic services provided and which distinguish providers and nonproviders of orthodontic services. Multiple regression analysis revealed that four practitioner characteristics explained 43% of the variance in the number of orthodontic patients treated. Dentists who treated more orthodontic patients (1) treated more general practice patients, (2) frequently used multiple sources to keep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Finally, orthodontic treatment provided by general dental practitioners is a debated issue between academics, dentists, and orthodontists. [ 16 17 ] There are two main stances: Either dental students should be taught basic skills, such as dealing with fixed orthodontics or handling simple interceptive orthodontic cases during their undergraduate program, or they should not. Those who hold the former viewpoint believe that the acquired skills will provide the community with well-trained dentists who can handle difficulties that they encounter in their practical life.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, orthodontic treatment provided by general dental practitioners is a debated issue between academics, dentists, and orthodontists. [ 16 17 ] There are two main stances: Either dental students should be taught basic skills, such as dealing with fixed orthodontics or handling simple interceptive orthodontic cases during their undergraduate program, or they should not. Those who hold the former viewpoint believe that the acquired skills will provide the community with well-trained dentists who can handle difficulties that they encounter in their practical life.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors influence orthodontic practices which include personal and practice characteristics of dentists. A study published in 2019 reported that there was a significant difference between the orthodontic care provider and non-orthodontic care provider -general dental practitioners (GDPs) -in terms of knowledge, attitude, and orthodontic needs among two groups of practitioners 3 . Their results pointed out and highlighted that continuous dental education programs and use of information resources play a valuable role in GDP and non-orthodontic specialists' education.…”
Section: Introductionmentioning
confidence: 99%